2017
DOI: 10.1093/aje/kwx274
|View full text |Cite
|
Sign up to set email alerts
|

Does the Type of Residential Housing Matter for Depressive Symptoms in the Aftermath of a Disaster? Insights from the Great East Japan Earthquake and Tsunami

Abstract: The 2011 Great East Japan Earthquake and Tsunami resulted in widespread property destruction and over 250,000 displaced residents. We sought to examine whether the type of housing arrangement available to the affected victims was associated with a differential incidence of depressive symptoms. In this prospective cohort study, which comprised participants aged ≥65 years from Iwanuma as a part of the Japan Gerontological Evaluation Study, we had information about the residents’ mental health both before the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 43 publications
2
42
0
Order By: Relevance
“…Compared with the nationwide prevalence of subjective toothache among the general population in Japan (1.8% in 2016), the total (3.7%) and highest prevalence (7.9%) observed among the GEJE survivors were potential factors to negatively impact the subjects’ health status. The most crucial finding was that significant association between the housing type and subjective toothache was observed only in the prefabricated temporary housing group, the most distressful residence . In contrast, a previous study indicated that favourable housing conditions may contribute psychological well‐being .…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Compared with the nationwide prevalence of subjective toothache among the general population in Japan (1.8% in 2016), the total (3.7%) and highest prevalence (7.9%) observed among the GEJE survivors were potential factors to negatively impact the subjects’ health status. The most crucial finding was that significant association between the housing type and subjective toothache was observed only in the prefabricated temporary housing group, the most distressful residence . In contrast, a previous study indicated that favourable housing conditions may contribute psychological well‐being .…”
Section: Discussionmentioning
confidence: 85%
“…Recently, people living in prefabricated housing tended to elderly, economically disadvantaged, and health status of prefabricated housing dwellers was exacerbated over time after the GEJE, possibly due to employment and income issues at postdisaster, which were potential factors associated with toothache . Therefore, socio‐demographic characteristics, lifestyle, and health condition variables were included in the analyses as covariates such as the subjects sex, age, subjective economic status, smoking habits (“Yes” or “No”), and psychological distress using the six‐item Kessler Psychological Distress Scale (K6), and insomnia using the eight‐item Athens Insomnia Scale (AIS‐8) …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations